An Evaluation of Parent Preference for Prompting Procedures - (:unkn) unknown (My University, 2018)
Previous researchers have suggested that parent participation in intervention can enhance intervention and promote generalization of skills across settings. Thus, parents should be trained to implement behavioral interventions. The purpose of the current investigation was to evaluate parent preference for and acceptability of three commonly used prompting procedures. Experimenters trained parents of children with disabilities to use three evidence-based prompting strategies (i.e., least-to-most, most-to-least, and a progressive prompt delay). Once the parent reached the mastery criteria with each prompting procedure, his/her preference for each of the strategies was evaluated using a concurrent-chains arrangement. Additionally, treatment acceptability of all procedures was measured multiple times throughout the study. All participants met the mastery criteria for each of the prompting procedures and showed a preference for least-to-most prompting. Results suggested that parents’ acceptability for procedures prior to training were different than post-training/post-child practice. In addition, acceptability rating scores obtained at the end of the investigation corresponded to preference of intervention during the concurrent-chains arrangement. The data obtained during this study support the utility of objective measures for studying preference for behavioral skill-acquisition procedures.
Keywords: concurrent-chains arrangement; parents; prompt fading